ISO 9001 in software-developing VSEs assisted by the COMPETISOFT Model - Esponda, Silvia (2012)
A reconciliation between the COMPETISOFT software process improvement model and the international standard ISO 9001 is presented. The purpose of this reconciliation is analyzing the possibility that small software development businesses, assisted by the generation of the documents and the control of the activities defined with the COMPETISOFT Model, can obtain the ISO 9001 standard certification for Project Management and Software Development Processes.